Social Connection Strategies Proposed by Ecuadorian Universities in the COVID-19 Setting - Vizcaíno Imacaña, Fernanda Paulina (2022)
This study compares the social connection strategies offered by the Ecuadorian universities in the COVID-19 setting. The main objective was to tackle the transition from face-to-face activities to virtual ones in order to accomplish a degree of continuity in their activities. The data-gathering was done during the 2020 period; the documental method’s criteria analysis was accomplished. For the purpose of completing the study, the inductive-deductive method was used to describe, in a general way, particular conditions present during the investigation. Thus, it can be demonstrated that higher-education institutions achieved the continuity of activities through tele-activity backed by the Information and Communication Technologies (ICTs), concluding in benefits for the society’s most vulnerable sectors. Finally, new studies which maintain this investigation as a basis are proposed, as a way to show results over more extensive periods of analysis.